Developing a Pandemic-Related Mental Health Micro-Collection for an Academic Library - Phares, Dee Anna (Library resources & technical services, 2025)
Academic library patrons dealing with the impact of trauma, depression, anxiety, or addiction spawned or exacerbated by the COVID-19 pandemic require materials that address the unique conditions that have shaped mental health since late 2019. This paper demonstrates how one academic library endeavored to address patrons' needs for mental health resources by developing a "Coping and COVID-19" micro-collection. The paper explores the process of creating and curating a small-scale topic-specific collection using a trauma-informed approach and highlights the importance not only of acquiring materials exploring pandemic-related conditions and praxis, but also gathering contemporary texts that provide a record of the historical moment and a window into the minds of a population attempting to cope with a public health crisis that initiated a mental health one. Ultimately, the paper contends that college and university libraries are well- positioned to deliver patron-responsive service to their campuses that promotes well-being and belonging.